Evaluasi Awal Kualitas Sistem Informasi Akademik dengan Metode EUCS - Dwi Cahya Septiandi, Indra; Iqbal, Fauzan Muhammad; Ulhaya, Shafia Syifa; Kamila, Ashila Rahmani (LPPM Universitas Putera Batam, 2026)
Academic InFormation Systems (AIS) are essential for supporting academic management and instructional processes in higher education institutions. Evaluating AIS quality from the perspective of end users is crucial to ensure system effectiveness, particularly when systems are used intensively by lecturers. This study aims to conduct an initial evaluation of AIS quality at Universitas Cipasung based on lecturers’ satisfaction using the End-User Computing Satisfaction (EUCS) model as a preliminary study. The study employed a quantitative survey design using an EUCS-based questionnaire encompassing five dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. Although the conceptual population consisted of 92 users (lecturers and administrative staff), valid responses were obtained from 11 lecturers. Given the limited sample size and ordinal data scale, data were analyzed using descriptive statistics and Spearman Rank Correlation to examine the relationship between EUCS dimensions and perceived AIS quality. The findings indicate that all EUCS dimensions achieved mean scores within the “satisfied” category. Spearman correlation analysis revealed that all dimensions were significantly associated with AIS quality (p < 0.05), with Format demonstrating the strongest correlation, followed by Content and Ease of Use. The results confirm that the EUCS model is applicable for preliminary evaluation of AIS quality. User interface design, inFormation relevance, and system usability emerge as critical factors influencing lecturers’ perceptions of system quality.